Pathways for an island energy transition under climate change: The case of Chongming Island, China - Song, Xuemei; Chen, Zhujun (Frontiers in Energy Research, 2023)
The normal operation of the energy system is related to the security and stability of the region and even the country. Compared with inland areas, islands can become a precedent for building a low-carbon and zero-carbon society due to geographic advantage. However, they also have to deal with more vulnerable energy systems. Taking Chongming Island as a case, this paper discusses the necessity of energy transformation from external, internal, and geographic causes, investigates the possible path of resilient energy transformation for islands, and puts forward a series of policy recommendations together with possible ways toward resilient energy transition.